2011
DOI: 10.1007/s10310-010-0211-z
|View full text |Cite
|
Sign up to set email alerts
|

Types of frass produced by the ambrosia beetlePlatypus quercivorusduring gallery construction, and host suitability of five tree species for the beetle

Abstract: We studied the biology of the ambrosia beetle Platypus quercivorus in the logs of five tree species to determine: (1) the relationship between the amount of frass produced by beetles and tunnel length, (2) the relationship between frass shape and the morphological characteristics of P. quercivorus mouthparts, and (3) the suitability of five tree species for P. quercivorus reproduction. Five logs each from healthy Quercus crispula, Q. serrata, Castanea crenata, Sorbus japonica, and Cryptomeria japonica trees we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 31 publications
1
38
0
Order By: Relevance
“…Tarno et al (2011) reported that fibrous frass indicated both male and female activity in the boring tunnel for reproduction. First a male makes a simple tunnel.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Tarno et al (2011) reported that fibrous frass indicated both male and female activity in the boring tunnel for reproduction. First a male makes a simple tunnel.…”
Section: Discussionmentioning
confidence: 99%
“…Adult males start the formation of galleries in June and females begin to deposit eggs at the terminal parts of tunnels two to three weeks after the commencement of gallery formation (Sone et al, 1998). More eggs are laid in healthy logs than infected logs by Raffaelea quercivora of Q. crispula, or in logs of any other tree species (Tarno et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations